PENGARUH PENERAPAN FRAUD EARLY WARNING SYSTEM (FEWS) TERHADAP AKTIVITAS BISNIS PERUSAHAAN - Wibowo Wibowo; Winny Wijaya (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2009)
Proposes of this observation is to know how big the effect of application of fraud early warning system to business activity that happen in acompany. Because of that, fraud needs more attention and how can fraud early warning system prohibit fraud happen in some business activity of one company. This observation did with spread the questioner to employees in a company to know how big the effect of this fraud early warning system. Data analysis is using simple regression method where test the quality of qualitative data using validity test and reliability test, hypothesis test using fit model testing and F tests. Based on the result of validity test and reliability test, get the valid and reliable result. Based on the result of fit model testing, get the result that the implementation of fraud early warning system is not effective in this company. This is show from R² value as 0.011, which means independent variable just available to clarify dependent variable as 1.1%. Meanwhile, from result of simultaneous simple regression testing, get that fraud early warning system is not significant affected its business activity. This is show from p-value as 0.996, which higher than alpha 0.05.